Cardiovascular risk profile in burn survivors. Issue 7 (November 2017) - Leung, Becky; Younger, John F.; Stockton, Kellie; Muller, Michael; Paratz, Jennifer
Highlights: Burn survivors had an increased level of triglycerides and a decreased level of high density lipoprotein (HDL) compared to normative values. These levels were not correlated with time since injury, age, dietary pattern or family history. The levels were correlated with total body surface area % of burn and level of physical activity reported. Abstract: Objective: Burn patients have prolonged derangements in metabolic, endocrine, cardiac and psychosocial systems, potentially impacting on their cardiovascular health. There are no studies on the risk of cardiovascular disease (CVD) after-burn. The aim of our study was to record lipid values and evaluate CVD risk in adult burn survivors. Methods: In a cross-sectional study patients ≥18 years with burn injury between 18–80% total burn surface area (TBSA) from 1998 to 2012 had total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL) and triglycerides measured via finger prick. Means were compared to optimal ranges. Multivariate regression models were performed to assess the association of lipids with age, years after-burn and total body surface area % (TBSA). A p value <0.05 was considered significant. The Framingham General Cardiovascular Risk Score (FGCRS) was calculated. Results: Fifty patients were included in the study. Compared to optimal values, patients had low HDL and high triglycerides. Greater %TBSA was associated with statistically significant elevation of triglycerides (p = 0.007) and total cholesterol/HDL ratio (p = 0.027). The median FGCRS was 3.9% (low) 10-year risk of CVD with 82% of patients in the low-risk category. Patients involved in medium/high level of physical activity had optimal values of HDL, TC/HDL and triglycerides despite the magnitude of TBSA%. Conclusion: Adult burn survivors had alterations in lipid profile proportional to TBSA, which could be modified by exercise, and no increase in overall formally predicted CVD risk in this cross sectional study.